Deep reactive ion etching of alumina titanium carbide using chlorine-based plasma - C. Pakpum (2018)
© 2016 Elsevier B.V. Al2O3-TiC (AlTiC) burnish head is widely used in hard disk drive manufacturing process to smoothen magnetic media surface produced from metal deposition process. Vertical etched wall of air bearing surface burnish head is ideal fabrication target since it provides fly height stability. Commonly used fluorine-based plasma etchant leads to an incline etched AlTiC wall due to redeposition of AlF3etch byproduct. This paper proposed the chlorine-based etching to improve etched wall profile due to etch byproduct volatility. A vapor pressure-temperature plot of potential etch byproducts in etching process was created to help design etching conditions that result in volatile etch byproducts. The BCl3/Cl2/Ar combinations were varied to obtain optimized etched wall profile, etch rate, and, etch selectivity between AlTiC and NiCr hard mask. It was found that 60 sccm BCl3: 60 sccm Cl2: 80 sccm Ar with 20 °C platen temperature and 5 mTorr processing pressure provided etched wall angle of 79° with 152 nm/min etch rate and 4.1:1 AlTiC:NiCr etch selectivity.